Buildings Structure Response Due to Railway Traffic - Bencat, Jan; Stypula, Krzysztof (Communications - Scientific letters of the University of Zilina, 2013)
The free–field dynamic response at the distance and dynamic response of building structures due to railway traffic calculation procedures is described in this paper. The viscoelastic halfspace model is used both for evaluation of the track–soil interaction forces as well as for prediction of the ground–borne vibrations spectral functions at the distance. In the next step these functions are applied for building structure dynamic response calculation via relevant computational building structure model.